Pengembangan Sipejala (Sistem Informasi Pelayanan Jasa Laundry) Dengan Model Rapid Application Development - Hidayati, Nur (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
The use of a good information system is necessary in providing services to customers. This is related to the level of satisfaction felt by customers with the choice of services used by companies or organizations. If the customer gets satisfaction in the services provided, it can give a deep impression to the customer and of course the customer will return to use his services. Laundry services are one type of service that is widely used by the wider community today. We have encountered many laundry places, but there are still many laundry places that use a manual system in providing services to customers. This of course can cause several problems such as difficulties in finding data, difficulties in reading data and making service reports takes a long time. If this is allowed to continue, of course it can have a negative impact on customers, where customers feel dissatisfied and uncomfortable with the services provided. So that customers will look for new places to get better laundry services. Therefore, it is necessary to improve the laundry service system so that it can solve the current problems. With the aim of providing the best service to customers and facilitating data processing of laundry services. To achieve this, it is necessary to use the right model in the development of its information system, one of which is the Rapid Application Development (RAD) model. By using this model, the best application program can be produced for the development of information systems for laundry services.